Adverse Perinatal Outcomes Associated with Stage 1 Hypertension in Pregnancy: A Retrospective Cohort Study - Norton, Elizabeth; Shofer, Frances; Schwartz, Hannah; Dugoff, Lorraine (American Journal of Perinatology, 2021)
Objective To determine if women who newly met criteria for stage 1 hypertension in early pregnancy were at increased risk for adverse perinatal outcomes compared with normotensive women.Study Design We conducted a retrospective cohort study of women who had prenatal care at a single institution and subsequently delivered a live infant between December 2017 and August 2019. Women with a singleton gestation who had at least two prenatal visits prior to 20 weeks of gestation were included. We excluded women with known chronic hypertension or other major maternal illness. Two groups were identified: (1) women newly diagnosed with stage 1 hypertension before 20 weeks of gestation (blood pressure [BP]: 130–139/80–89 on at least two occasions) and (2) women with no known history of hypertension and normal BP (<130/80 mm Hg) before 20 weeks of gestation. The primary outcome was any hypertensive disorder of pregnancy; secondary outcomes were indicated preterm birth and small for gestational age. Generalized linear models were used to compare risk of adverse outcomes between the groups.Results Of the 1,630 women included in the analysis, 1,443 women were normotensive prior to 20 weeks of gestation and 187 women (11.5%) identified with stage 1 hypertension. Women with stage 1 hypertension were at significantly increased risk for any hypertensive disorder of pregnancy (adjusted risk ratio [aRR]: 1.86, 95% confidence interval [CI]: 1.12–3.04) and indicated preterm birth (aRR: 1.83, 95% CI: 1.12–3.02). Black women and obese women with stage 1 hypertension were at increased for hypertensive disorder of pregnancy compared with white women and nonobese women, respectively (aRR: 1.32, 95% CI: 1.11–1.57; aRR: 1.69, 95% CI: 1.39–2.06).Conclusion These results provide insight about the prevalence of stage 1 hypertension and inform future guidelines for diagnosis and management of hypertension in pregnancy. Future research is needed to assess potential interventions to mitigate risk.Key Points
Keywords: American College of Cardiology; American Heart Association; chronic hypertension; gestational hypertension; hypertensive disorder; preeclampsia; preterm birth; small for gestational age